Techno-Economic Analysis of Residential Grid-Connected Rooftop Solar PV Systems in Indonesia Under MEMR 26/2021 Regulation - Tarigan, Elieser (International Journal of Energy Economics and Policy, 2024)
Grid-connected commercial rooftop solar PV systems have been widely used worldwide to provide affordable, clean energy and long-term energy security solutions. This is especially true in cities where space is limited and rooftops are not being used. According to the Ministry of Energy and Mineral Resources (MEMR) No 26/2021 regulation in Indonesia, the rooftop PV system is allowed to be integrated with electricity grid with an export-import metering. The owner of the rooftop PV system will not only reduce their electricity bill, but also offset the energy over a period of 10 years. This paper provides a design and sizing analysis of a small scale rooftop solar PV system for residential. This study uses the PVsyst and SolarGIS tools to estimate the amount of energy produced by a 3 kWp solar system. It also provides a financial evaluation of the system’s profitability, with particular attention to commercial buildings that are covered under MEMR regulation. This detailed analysis can be used by asset owners to decide the best way forward in terms of sustainable energy production and cost savings, as well as addressing the energy security problem.